2019
DOI: 10.2147/cmar.s206033
|View full text |Cite
|
Sign up to set email alerts
|

<p>High dose vs low dose irradiation of the subventricular zone in patients with glioblastoma—a systematic review and meta-analysis</p>

Abstract: Purpose The published data indicate that the irradiation of the subventricular zone (SVZ) might play a role in the treatment of patients with glioblastoma (GBM). We aimed to determine whether radiation treatment doses (high vs low) applied to the SVZ can lead to an increase in progression free survival (PFS) and overall survival (OS). Patients and methods We undertook a systematic review and meta-analysis according to the PICOS research criteria of patients with gliobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The prognostic difference could theoretically stem from intrinsic characteristics of the tumor, or from its SVZ-contacting or SVZ-distal location. At this time, there is no conclusive evidence that links the clinical features of SVZ+ GBM to a defined molecular subtype or other intrinsic tumor characteristic ( 35 ). Although some have shown a differential distribution of GBM subtype in preferential brain regions ( 36 ), a recent work found no differences in molecular signature in tumor bulk tissue from SVZ+ or SVZ– tumors ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic difference could theoretically stem from intrinsic characteristics of the tumor, or from its SVZ-contacting or SVZ-distal location. At this time, there is no conclusive evidence that links the clinical features of SVZ+ GBM to a defined molecular subtype or other intrinsic tumor characteristic ( 35 ). Although some have shown a differential distribution of GBM subtype in preferential brain regions ( 36 ), a recent work found no differences in molecular signature in tumor bulk tissue from SVZ+ or SVZ– tumors ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the reported effect of SVZ irradiation on outcomes in GBM patients has been inconsistent. In a meta-analysis of four studies observing the effects of high vs lose dose radiation on prognosis, increased radiation dose to the ipsilateral SVZ significantly increased PFS while failing to significantly improve OS ( 217 ). Irradiation dose to the contralateral SVZ did not significantly improve PFS.…”
Section: Neural Stem Cells In the Subventricular Zone Implication In ...mentioning
confidence: 99%
“…Contralateral SVZ radiation dose effect on OS was not analyzed as it did not meet the study’s inclusion criteria. Higher cutoffs for “high dose irradiation” in the various studies correlated with increased PFS and OS as compared to lower cutoffs ( 217 ). Gupta et al.…”
Section: Neural Stem Cells In the Subventricular Zone Implication In ...mentioning
confidence: 99%
“…Recent studies suggested that patients with GBMs in contact with the lateral ventricle-SVZ region have lower survival rates than those with GBMs contacting the subgranular zone, corpus callosum, or cortex[ 16 , 17 ]. Furthermore, Şuşman et al [ 69 ] found a significant difference in the PFS of patients with GBM who were administered with high radiotherapy doses within the LV-SVZ region. Chen et al [ 70 ] investigated 102 patients with GBM who had undergone surgical resection followed by adjuvant intensity-modulated radiation therapy and concomitant TMZ, and found that the recurrence of GBM was significantly related to the proximity to neurogenic regions (SVZ)[ 70 ].…”
Section: Mechanism Of Svz Nscs In Glioblastomamentioning
confidence: 99%